Profile of patients admitted with rabies in Epidemic Disease Hospital of Mysore, India - Khan, Mudassir Azeez; Joe, Prathyusha; M., Pashupathy; M., Laxman (International Journal Of Community Medicine And Public Health, 2018)
Background: Rabies is the only communicable disease of man that is 100 percentage fatal, yet it is easily preventable with timely and appropriate administration of vaccine and immunoglobulin. Rabies is still a neglected disease and the study was undertaken to determine the socio-demographic, clinical profile and the immunisation status of patients admitted with rabies in Epidemic Disease hospital, Mysore. Methods: The study was done retrospectively by observation of case records and registers for a period of ten years from 2008 to 2017. Results: Case records of 44 patients admitted with rabies were obtained. Most of them were males above the age of 40 years and reported history of dog bite (72.7%). Majority had symptoms 1-2 months after the animal bite. The classical symptoms of hydrophobia were present in 86.4% patients. All the 44 patients expired in the hospital. None of them had a complete post exposure prophylaxis of antirabies vaccination and immunoglobulin. The reasons for the same were obtained from case records and by interviewing the doctor in charge. The non-availability of vaccine and immunoglobulin, decreased knowledge and expertise in administration of immunoglobulin among hospital staff in the periphery were some of the reasons. Conclusions: The cost incurred, loss of wages and not understanding the importance of completion of anti-rabies vaccination by the animal bite victims can be addressed only by providing the immunoglobulin and vaccine at very low costs, adequate training of doctors and ensuring the availability of vaccine and drugs.